HUBUNGAN ANTARA DUKUNGAN KELUARGA DENGAN KEMAMPUAN MELAKUKAN PERAWATAN PALIATIF ANAK KANKER DI RUMAH SINGGAH YAYASAN PEDULI KANKER ANAK BALI - Fatmiwiryastini, Ni Putu Sri; Utami, Kadek Cahya; Swedarma, Kadek Eka (Coping: Community of Publishing in Nursing; Vol 9 No 4 (2021): Agustus 2021, 2021)
Cancer is the leading cause of death of children and adolescents in the world. Children with cancer experience various problems both physical and psychological that affect the quality of life of the patient, so it needs holistic treatment or known as palliative care. Palliative care is a community-based treatment to improve the quality of life of children with cancer. Parents have an important role in providing palliative care for children with cancer. This study aims to determine the correlation family support and the ability to perform palliative care of cancer children. This study is used a cross sectional correlative descriptive design selected by accidental sampling technique. The questionnaire used was a demographic questionnaire, a family support questionnaire and a palliative care ability questionnaire. The results of this study indicate 70% of respondents have less family support and 45% of respondents have good palliative care abilities. This study resulted that there is a  significant strong and positive correlation the level of family support and the ability of parents to do palliative care for cancer children (p value = 0.001; r = 0.664; a  = 0.05). Based on these results it is hoped that family can increase the provision of support so as to improve the ability of palliative care of cancer children.